Monocytic myeloid‐derived suppressor cells reflect tuberculosis severity and are influenced by cyclooxygenase‐2 inhibitors. Issue 1 (6th November 2020) - Jøntvedt Jørgensen, Marthe; Jenum, Synne; Tonby, Kristian; Mortensen, Rasmus; Walzl, Gerhard; Du Plessis, Nelita; Dyrhol‐Riise, Anne Ma
Abstract: Myeloid‐derived suppressor cells (MDSCs) increase in tuberculosis (TB) and may be targets for host‐directed therapy (HDT). In this study, we use flow cytometry to analyze the effects of cyclooxygenase‐2 inhibitors (COX‐2i) on monocytic (M)‐MDSCs in blood from TB patients attending a clinical trial of COX‐2i. The effects of COX‐2i on M‐MDSCs and mycobacterial uptake were also studied by an in vitro mycobacterial infection model. We found that M‐MDSC frequencies correlated with TB disease severity. Reduced M‐MDSC ( P  = 0.05) and IDO ( P  = 0.03) expression was observed in the COX‐2i group. We show that peripheral blood‐derived M‐MDSCs successfully internalized Mycobacterium bovis and that in vitro mycobacterial infection increased COX‐2 ( P  = 0.002), PD‐L1 ( P  = 0.01), and Arginase‐1 ( P  = 0.002) expression in M‐MDSCs. Soluble IL‐1β, IL‐10, and S100A9 were reduced in COX‐2i‐treated M‐MDSCs cultures ( P  < 0.05). We show novel data that COX‐2i had limited effect in vivo but reduced M‐MDSC cytokine production in vitro. The relevance of COX‐2i in a HDT strategy needs to be further explored. Graphical Abstract: Study of Cyclooxygenase‐2 inhibitors effects on monocytic Myeloid‐derived suppressor cells in host directed therapy clinical trial supported by in‐vitro data with reduction of suppressive soluble markers.